Two equations are given below:
1 answer:
Answer:
(-11,-9)
Step-by-step explanation:
b-2-3b=16
-2b-2=16
-2b=18
b= -9
a= -9-2
a=-11
You might be interested in
212 + 28% = <span>271.36</span>
<span>Hope it helps! :D</span>
Answer:
Step-by-step explanation:
u put the gs with each other by flipping the one that was changed
3.6g-1.6g=8-2
2g=6
g=6/2
g=3
The answer is absolute dictator
So it would be 49+(20)+8
= 77
Answer:
<h3>p(+)q=SQR(p^2+q^2)</h3>
8(+)6=SQR(8^2+6^2)
SQR(64+36)
SQR(100)
=10
Step-by-step explanation:
p + Q is equal to square root of p square + Q Square
sqr means square root